2017
DOI: 10.1007/s00394-017-1597-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bovine colostrum supplementation on in vivo immunity following prolonged exercise: a randomised controlled trial

Abstract: Background Bovine colostrum (COL) has been advocated as a nutritional countermeasure to exercise-induced immune dysfunction, but there is a lack of research with clinically relevant in vivo measures. Aim To investigate the effects of COL supplementation on in vivo immunity following prolonged exercise using experimental contact hypersensitivity (CHS) with the novel antigen diphenylcyclopropenone (DPCP). Methods In a double-blind design, 31 men were randomly assigned to COL (20 g/day) or placebo (PLA) for 58 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…Our findings support and extend previous work by Coombes et al who examined changes in plasma IGF-1 in response to 20-60 g per day of colostrum for 8 weeks and found no increase [7]. Similar negative results have been reported by others following ingestion of 20 g or 60 g/day of colostrum or whey, also for 8 weeks [23][24][25]. In contrast, Mero et al reported that colostrum ingestion does increase IGF-I levels [26] although there were methodological and interpretation issues as the only significant effect seen was comparing the change in IGF-1 levels from baseline, due to the placebo arm falling by 18 ng/ml and the colostrum-treated group increasing by 28 ng/ml) [26].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings support and extend previous work by Coombes et al who examined changes in plasma IGF-1 in response to 20-60 g per day of colostrum for 8 weeks and found no increase [7]. Similar negative results have been reported by others following ingestion of 20 g or 60 g/day of colostrum or whey, also for 8 weeks [23][24][25]. In contrast, Mero et al reported that colostrum ingestion does increase IGF-I levels [26] although there were methodological and interpretation issues as the only significant effect seen was comparing the change in IGF-1 levels from baseline, due to the placebo arm falling by 18 ng/ml and the colostrum-treated group increasing by 28 ng/ml) [26].…”
Section: Discussionsupporting
confidence: 93%
“…BC contains both specific immune factors (e.g., IgGs) and non-specific immune modulatory and antimicrobial factors (e.g., lactoferrin), with each component potentially having relevance for immune modulation. There is now extensive data showing that BC may have value for preventing and treating microbial infections, e.g., [ 67 ], working via the hosts immune function [ 68 ], in addition to attacking the microbe itself. As an example, volunteers given BC at the same time as receiving attenuated oral Salmonella typhi Ty21a vaccine produced increased levels of circulating specific IgA compared to controls who did not receive BC [ 69 ].…”
Section: Constituents Of Bcmentioning
confidence: 99%
“…This suggests that the primary immune response to antigens (APC and induction of T cell specific memory) is more susceptible to the perturbations induced by prolonged exercise than responses to recall (previously exposed) antigens, which may have relevance regarding the susceptibility of athletes to new/ novel compared to nonnovel pathogens. A number of follow-up studies using the CHS model have since demonstrated that this is a controllable, reproducible, sensitive, and valid in vivo marker of exercise-induced immunodepression (Diment et al, 2015;Davison et al, 2016;Jones et al, 2017). The study by Diment et al (2015) also demonstrated no effect of the same exercise (2 h of treadmill running) on the skin's response to the irritant croton oil, which provided strong evidence that the observed decrease in in vivo immunity assessed by this CHS method of immune induction to DPCP is an antigen-specific, T-cell-mediated, response.…”
Section: Strenuous or Intensive Exercisementioning
confidence: 99%